2014
DOI: 10.1177/1557988314532285
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Preventive Health Behaviors Among Non-Hispanic White Men

Abstract: The objectives of this study were to estimate and compare the age-adjusted prevalence of not receiving a flu vaccine, pneumonia vaccine, or prostate cancer screening among U.S.- and foreign-born White men by region of birth (Europe/Russia and the Arab Nations) and examine these associations while controlling for potential confounders. Twelve years of restricted data from the National Health Interview Survey (NHIS) including 91,636 U.S.- and foreign-born men were used. Chi-squares were used to compare descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previous studies on influenza vaccination prevalence among foreign-born Arab Americans in National Health Interview Surveys found that Arab Americans were less likely to report influenza vaccination than NHW [13,14]. Dallo and Kindratt reported an odds ratio of 0.48 for vaccination among foreign-born Arab American women and an odds ratio of 0.42 for vaccination among foreign born Arab American males in unadjusted models when compared to NHW [13,14].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies on influenza vaccination prevalence among foreign-born Arab Americans in National Health Interview Surveys found that Arab Americans were less likely to report influenza vaccination than NHW [13,14]. Dallo and Kindratt reported an odds ratio of 0.48 for vaccination among foreign-born Arab American women and an odds ratio of 0.42 for vaccination among foreign born Arab American males in unadjusted models when compared to NHW [13,14].…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, only two previous studies have examined influenza vaccine uptake among Arab Americans [13,14]. Based on 12 years of data obtained from the National Health Interview Survey, foreign-born Arab Americans were less likely to receive the influenza vaccine than both foreign-born and US-born Whites [13,14]. However, both studies only considered data up until 2011, were solely focused on foreign-born Arab Americans, and used fairly small sample sizes (238 males, and 205 females).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using national data sources have reported low levels of education among foreign-born MENA adults ranging from 18-32.8% (11,13,(25)(26)(27)(28)(29)(30)(31). When strati ed by sex, studies showed that 22.7-26.7% of foreign-born MENA women (13,32) and 11% of foreign-born MENA men had less than high school education (13,33).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used NHIS data to uncover health outcomes among foreign-born Middle Eastern and Arab American immigrant populations (11,13,25,26,(29)(30)(31)(32)(33). By linking with MEPS, we accessed additional health information from a subsample of participants who completed the previous year's NHIS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Screening for depression is generally conducted at "initial visits" or "annual visits" and rarely at urgent/sick visits. Many Arab Americans visit the doctor when they are sick rather than for preventive or screening reasons (Dallo & Kindratt, 2015a, 2015b. Therefore, this may explain the lower estimate of being offered/completing a PHQ-9 among Arab Americans compared to other racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%